PENGARUH KEMAMPUAN MANAJERIAL DAN KETELADANAN KEPALA MADRASAH TERHADAP KINERJA GURU MTs SWASTA KECAMATAN PONDOK AREN - Amin; Suciati; Rismita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to find out and analyze the effect of: 1) the managerial ability of the madrasa principal on teacher performance, 2) the example of the madrasa head on teacher performance, 3) the effect of managerial ability and the example of the madrasa principal simultaneously on the performance of teachers at Private MTs Pondok Aren District. This research is quantitative research using survey method and analytic descriptive approach. The population that became the object of research were all private madrasah tsanawiyah (MTs) teachers with a total sample of 145 teachers. Collecting data through the distribution of questionnaires. The data analysis technique used is correlation and regression techniques. The results of the data analysis show that: 1) there is a significant effect of the managerial ability of the madrasah head on teacher performance of 33.68%, 2) there is a significant effect of the exemplary head of the madrasa on teacher performance of 7.08%, 3) there is an effect of managerial ability and the simultaneous example of the madrasah principal on teacher performance is 40.8%, the better the managerial ability and exemplary principal of the madrasah, the teacher's performance will increase. These findings imply that the managerial ability and example of the madrasah principal are two factors that have an influence on teacher performance, but there are many other factors that influence the performance of MTs swasta teachers in Pondok Aren District.